The method to select the transport path based on the multimodal cost - Cheng, Yaorong (Transport, 2012)
To begin with, the current paper introduces the meaning of freight multimodal transport in order to select the best transport path in multimodal network. Secondly, the forming mechanism of freight multimodal transport cost has been illustrated. In addition to that the construction and the character of the freight multimodal cost have been analyzed carefully, and the mathematics model is set up so that to figure out the total cost of multimodal. Finally, a case of multimodal is given out and analyzed. The results indicate that the model and way to select the best multimodal path in the multimodal network are reasonable and effective. First Published Online: 26 Jun 2012